Exciplex electroluminescence spectra of the new organic materials based on zinc complexes of sulphanylamino-substituted ligands - Nikitenko, S.L.; Krasnikova, S.S.; Kaplunov, M.G.; Yakushchenko, I.K. (Functional Materials, 2012)
Electroluminescence spectra of the devices based on the new zinc complexes of amino-substituted benzothiazoles and quinolines containing C-N-M-N chains in their chelate cycles have been investigated. The obtained spectra exhibit strong exciplex bands in green-yellow region 540-590 nm due to interaction of the excited states of zinc complexes and triarylamine molecules of hole-transporting layer. For some devices the intrinsic luminescence band in blue region 460 nm is also observed along with the exciplex band that results in almost white color of the device emission. The exciplex band can be eliminated if the material of the hole-transporting layer is not triarylamine derivative.